Bed utilisation and increased risk of Clostridium difficile infections in acute hospitals in England in 2013/2014. Issue 6 (6th September 2016) - Vella, Venanzio; Aylin, Paul P; Moore, Luke; King, Alice; Naylor, Nichola R; Birgand, Gabriel J C; Lishman, Hannah; Holmes, Alison
Abstract : Background: The study aimed to identify thresholds for hospital bed utilisation which are independently associated with significantly higher risks for Clostridium difficile infections (CDI) in acute hospitals in England. Method: A retrospective analysis was carried out on reported data from the English National Health Service (NHS) for the financial year 2013/2014. Reported rates of CDI were used as a proxy for hospital infection rates in acute NHS hospital trusts. Multivariate linear regression was used to assess the relationship between bed utilisation values and CDI controlling for confounding factors. Hospitals were finally plotted in a Pabon Lasso graph according to their average bed occupancy rate (BOR) and bed turnover rate (BTR) per year to visualise the relationship between bed utilisation and CDI. Results: Among English hospital NHS trusts, increasing BTR and decreasing BOR were associated with a decrease in CDI. However, this effect was not large, and patient mix had a larger impact on CDI rates than bed utilisation. Conclusions: While policymakers and managers wishing to target healthcare providers with high CDI rates should look at bed utilisation measures, focusing on these alone is unlikely to have the desired impact. Instead, strategies to combat CDI must take a wider perspective on contributory factors at the institutional level.